2010
DOI: 10.1016/j.neuroscience.2009.10.054
|View full text |Cite
|
Sign up to set email alerts
|

Differential distribution of exchange proteins directly activated by cyclic AMP within the adult rat retina

Abstract: The recently discovered exchange protein directly activated by cAMP (Epac), a guanine exchange factor for the G-protein RAP-1, is directly activated by cAMP independently of PKA. While cAMP is known to be an important second messenger in the retina, the presence of Epac has not been investigated in this tissue. The goal of the present study was to determine if the Epac1 and Epac2 genes are present and to characterize their location within the retina. Western blot analysis revealed that Epac1 and Epac2 proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 96 publications
0
18
1
Order By: Relevance
“…We observed 3 isoforms (α, β, and δ) of CaM Kinase II, with equimolar amounts of α and β and twice as much of the δ isoform. EPAC2 is expressed in photoreceptors 45 ; it is known to be involved in cAMP mediated vesicle release 46 and is a binding partner of Piccolo 17 and Rim 47 . Piccolo also binds L-TYPE Ca Channels 17 and an Actin-Binding Protein 48 providing a possible link between members in the presynaptic complex.…”
Section: Resultsmentioning
confidence: 99%
“…We observed 3 isoforms (α, β, and δ) of CaM Kinase II, with equimolar amounts of α and β and twice as much of the δ isoform. EPAC2 is expressed in photoreceptors 45 ; it is known to be involved in cAMP mediated vesicle release 46 and is a binding partner of Piccolo 17 and Rim 47 . Piccolo also binds L-TYPE Ca Channels 17 and an Actin-Binding Protein 48 providing a possible link between members in the presynaptic complex.…”
Section: Resultsmentioning
confidence: 99%
“…Epac1 is expressed in many retinal cell types (Whitaker and Cooper, 2010). To delineate in which cell type Epac1 expression is responsible for ischemic injury-induced retinal neuron death, we conditionally deleted Epac1 in myeloid/microglia and astrocytes using the Cre-loxP system.…”
Section: Epac1 In Microglia/myeloid Cells and Astrocytes Is Dispensabmentioning
confidence: 99%
“…Epac1 is ubiquitously expressed in tissues and often involved in pathologic conditions such as cardiac hypertrophy, heart failure, pain perception, and obesity, while Epac2 regulates physiological processes including insulin secretion, learning, and memory (Breckler et al, 2011;Okumura et al, 2014;Srivastava et al, 2012;Wang et al, 2013;Yan et al, 2013;Zhang et al, 2009). In the retina, Epac1 is expressed in retinal layers containing neurons (Whitaker and Cooper, 2010), but its pathophysiological role is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Both Epac1 and Epac2 are expressed in the retina [19]. It has been shown that Epacs have a profound role in cognition, loss of Epacs leads to impairment in memory retrieval in a fear conditioning paradigm [34], and it is also noted that in depressed patients, the Epac2 expression but not Epac1 is altered in the cortex [35].…”
Section: Epac2mentioning
confidence: 99%
“…Epac2 participates in the modulation of neuronal activities, including neurotransmitter release and synaptic plasticity [1517]. Both Epac1 and Epac2 are expressed in the brain [18], and retina [19], which is part of central nervous system (CNS) and can be viewed using non-invasive methods.…”
mentioning
confidence: 99%